Generation of an iPSC-line (BIONi010C-48) with restored P-glycoprotein functionality following transfection with the human MDR1 gene in the AAVS1 locus - Amanda Kongstad Redke Nielsen; Laura Lilieholm-Røngren; Benjamin Schmid; Bjørn Holst; Birger Brodin; Lasse Saaby (Stem Cell Research, 2024)
The human MDR1 gene encodes the efflux transporter P-glycoprotein, which plays an important part of the blood–brain barrier function of brain microvascular endothelial cells (BMECs). Here, we report the generation of an iPSC line, where a construct of the human MDR1 gene was inserted into the safe-site locus AAVS1. This iPSC line (BIONi010-C-48) shows functional expression of P-gp and can further be differentiated and cultured into electrically tight BMEC-like monolayers exhibiting polarized expression of P-gp in the apical membrane.